2016
DOI: 10.1177/0959353516636149
|View full text |Cite
|
Sign up to set email alerts
|

“I thought he was ugly”: Mothers of extremely premature children narrate their experiences as troubled subjects

Abstract: This article explores the ways in which mothers of extremely premature children make sense of their negative feelings towards their newborn child and their strategies for performing “proper motherhood”. The analysis was guided by discursive psychology and the feminist debate on attachment, mother–infant bonding, and “good motherhood”. The empirical material was created within a sub-study that set out to explore mothers’ and fathers’ experiences of having a premature child and was part of a project investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…For the substudy, we recruited the parents of moderately preterm children consecutive from the main study, as well as the parents of extremely preterm children from a separate, already completed, study called the Extremely Preterm Infants in Sweden Study (the EXPRESS study). These children were born between 2004–2005 at 22–26 weeks' gestation (see (Widding & Farooqi, )). It has been shown that two‐thirds of these extremely preterm children had a normal development or mild disabilities at 6.5 years of age, but the group as a whole had lower mean scores in motor function, language and cognitive tests, compared with the children born at term (Serenius et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the substudy, we recruited the parents of moderately preterm children consecutive from the main study, as well as the parents of extremely preterm children from a separate, already completed, study called the Extremely Preterm Infants in Sweden Study (the EXPRESS study). These children were born between 2004–2005 at 22–26 weeks' gestation (see (Widding & Farooqi, )). It has been shown that two‐thirds of these extremely preterm children had a normal development or mild disabilities at 6.5 years of age, but the group as a whole had lower mean scores in motor function, language and cognitive tests, compared with the children born at term (Serenius et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have described parents who perceive the preterm birth as chaos that causes stress and feelings such as fear, worry, helplessness, powerlessness, and guilt (e.g., Bolch et al, 2012;Fegran et al, 2008;Goutaudier et al, 2011;Hall, 2005). Parents of extremely preterm children have also expressed that they found seeing their children for the first time to be traumatic, had difficulty relating to their babies (Widding & Farooqi, 2016), and feared that their children would become attached to their nurses (Goutaudier et al, 2011). Worries regarding the children's health and the risk of death can also make it hard for parents to relate to their newborns (Erlandsson & Fagerberg, 2004;Fegran et al, 2008;Jackson et al, 2003;Swartz, 2005).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…The transition to motherhood is a journey wrought with psychological and interpersonal stress; these stressors are magnified following high‐risk pregnancies and premature births. Mothers describe feelings of tumultuous emotions on birthing their children prematurely (Hall, Kronborg, Aagaard, & Brinchmann, ; Holditch‐Davis et al., ; Sommer & Cook, ), and have likened their baby's recovery in the neonatal intensive care unit (NICU) to a roller‐coaster (Hummel, ), and described the experience as “being in hell” (Widding & Farooqi, , p. 160). Although studies detail the initial homecoming experience following a baby's NICU discharge, a paucity of literature explores the long‐term impact of preterm birth on mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Orfali, 2004;Vermeulen, 2004) oder aber dem Beziehungsaufbau unter den Bedingungen der Ungewissheit des (Weiter-)Lebens (z.B. Navne et al, 2017;Widding und Farooqi, 2016) auseinandersetzt, wird die Konstitution der Frühgeborenen-Intensivstation v.a. vonseiten der Science und Technology Studies (STS) thematisiert; hier ist besonders Mesman sehr aktiv (u.a.…”
Section: Introductionunclassified
“…Vor allem in einem Unterbereich der medical anthropology wird dieser Aspekt untersucht (z.B Navne et al, 2017;Widding und Farooqi, 2016)…”
unclassified